Detection of PIK3CA Mutations in Breast Cancer Bone Metastases. (30th August 2012) - Daneshmand, Manijeh; Hanson, Jennifer E. L.; Nabavi, Mitra; Hilton, John F.; Vandermeer, Lisa; Kanji, Femina; Dent, Susan F.; Clemons, Mark; Lorimer, Ian A. J.
Abstract : Background . An important goal of personalized cancer therapy is to tailor specific therapies to the mutational profile of individual patients. However, whole genome sequencing studies have shown that the mutational profiles of cancers evolve over time and often differ between primary and metastatic sites. Activating point mutations in the PIK3CA gene are common in primary breast cancer tumors, but their presence in breast cancer bone metastases has not been assessed previously. Results . Fourteen patients with breast cancer bone metastases were biopsied by three methods: CT-guided bone biopsies; bone marrow trephine biopsies; and bone marrow aspiration. Samples that were positive for cancer cells were obtained from six patients. Three of these patients had detectable PIK3CA mutations in bone marrow cancer cells. Primary tumor samples were available for four of the six patients assessed for PIK3CA status in their bone metastases. For each of these, the PIK3CA mutation status was the same in the primary and metastatic sites. Conclusions . PIK3CA mutations occur frequently in breast cancer bone metastases. The PIK3CA mutation status in bone metastases samples appears to reflect the PIK3CA mutation status in the primary tumour. Breast cancer patients with bone metastases may be candidates for treatment with selective PIK3CA inhibitors.